(untitled) (Global Business Management Review (GBMR), 2021)
Over the past decade, HR managers have been much concerned about the demographic changes and advised to take positive approaches to the management of organizations. These changes significantly cause population aging globally, resulting in economic and social challenges. This study aims to examine older workers’ retention, policy adjustment, and the aging workforce in Thailand. Purposive sampling was used to select a total of 520 respondents higher education institutions. We found that despite the call to retaining older workers, the majority of employers exhibit stereotypic attitudes, and finding it difficult to retain and attract older workers. Even though there have been initiatives toward discrimination legislation concerning older workers, however, policymakers should be proactive. Government should need to develop policies that would permit increased levels of older workers’ retention and create better competencies in achieving planned economic goals. Organizations need to adopt strategic approaches to age management and labor unions must show great commitment to the campaign against age discrimination.